Analysis of Edible Snail (Archachatina margtnata) Marketing in Ibadan Metropolis, Oyo State, Nigeria (2012)
The study examined the marketing efficiency, profitability and the factors contributing to the profitability of snail marketing in Oyo State Nigeria. Forty copies of questionnaires were administered in five major markets in Ibadan (Aleshinloye, Oje, Orita-merin, Bodija and Apata markets). Simple descriptive analyses such as percentage and frequency table were used to describe the socio-demographic characteristics of the respondents while multiple regression analysis was used to examine the determinants of profitability of snail marketing. It was discovered from the empirical result that 90% of the sellers were female while 10% were male. One hundred percent (100%) of the sellers were 20years of age and above, and have 10 or more years of experience, 37% had no formal education while 40% had primary education and 23% had secondary education. The average profit N24, 250 forms the Budgetary Analysis (Av.selling price -Av.cost price) while the marketing efficiency for different markets are 1.98, 1.54, 1.19, 1.25 and 1.60 for Aleshinloye, Oje, Oritamerin, Bodija and Apata respectively. Four regression functions (Linear Function, Semi log, double log and Exponential Function) were run to analyze the determinants of snail marketing profitability. The exponential function provided the best of fit equation because it has more significant variables, highest coefficient of multiple regression, R\0.66) and lowest DurbinWatson, DW (l.473).The marketing of Snail can be said to be profitable, efficient and sustainable. It can reduce poverty. Therefore, further research should be carried out to domesticate and rear more edible snails in Oyo State and Nigeria as a whole to get more supply of protein and calcium in our diets.